BIMBINGAN KELOMPOK MODEL PERMAINAN BELAJAR BERSIKAP UNTUK MENINGKATKAN KEMAMPUAN PENYESUAIAN DIRI DI SEKOLAH SISWA - Leksana, Dinar Mahdalena (JCE (Journal of Childhood Education), 2018)
The goal of this research was to test the effectiveness of using groupguidance service with learn to behave game to increase the ability of selfadjustment at school. This research was conducted by pre-test post-test one groupdesign. The subject of this research were eight students of 7th graders at MTsDarrul Maâarif Payaman, with low score of the ability of self adjustment atschool. Data analysis technique used in this research was Wilcoxonâs signed ranktest. It was found that there was a significant difference between the ability of selfadjustment at school score before and after treatment. Based on the Wilcoxon testit was found that T count = 0, N = 8 with 0,05 significant level so T table = 4. Itmeans T count < T table (0<4). So hypothesis of this research was accepted. Itcan be concluded that group guidance service with learn to behave game was aneffective approach to help students to increase the ability of self adjustment atschool.